OBJECT-ORIENTED PARTS INVENTORY INFORMATION SYSTEM MODELING USING UNIFIED MODELING LANGUAGE - Asrin, Fauzan (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
The availability of spare parts in a vehicle service workshop needs to be correctly recorded and recorded, making it easier for workshop owners to ensure the complete availability of vehicle spare parts. From the results of the author's observations, the Rizki Prima workshop has several obstacles in recording the availability of spare parts where the business processes being carried out are still a hassle for the employees working in the workshop. The problem often occurs when recording is the incompleteness of data related to incoming and outgoing goods. So the recording made in the ledger needs to be more accurate and requires a relatively long time to search one by one in the register if the workshop owner needs it. As a result of poor recording of goods, it is difficult for the owner to order goods again, worried that duplicating data will record incoming goods. The above problems are the basis for the authors to conduct research by utilizing information systems and modeling with an object-oriented approach using a unified modeling language to design a spare parts inventory information system according to user needs. To provide an overview of the Rizki Prima workshop transforming from conventional spare parts data recording to digital spare parts recording. The above problems are the basis for the authors to conduct research by utilizing information systems and modeling with an object-oriented approach using a unified modeling language to design a spare parts inventory information system according to user needs. To provide an overview of the Rizki Prima workshop transforming from conventional spare parts data recording to digital spare parts recording. The above problems are the basis for the authors to conduct research by utilizing information systems and modeling with an object-oriented approach using a unified modeling language to design a spare parts inventory information system according to user needs. To provide an overview of the Rizki Prima workshop transforming from conventional spare parts data recording to digital spare parts recording. KEYWORDS: Modeling, Information Systems, Spare Parts Inventory, Availability, Unified Modeling Language